Penetration of the blood–brain barrier by avitinib and its control of intra/extra-cranial disease in non-small cell lung cancer harboring the T790M mutation. (August 2018) - Wang, Hanping; Zhang, Li; Hu, Pei; Zheng, Xin; Si, Xiaoyan; Zhang, Xiaotong; Wang, Mengzhao
Highlights: Avitinib is a novel third-generation EGFR TKI. Avitinib is well tolerated and efficacious in T790M-positive patients. The penetrability of avitinib to the BBB is weak. Avitinib could control of asymptomatic brain metastases to a certain extent. Abstract: Background: Avitinib is an oral, potent, irreversible epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor selective for the EGFR T790 M mutation. We report the safety, intra-/extracranial efficacy, and the blood–brain barrier (BBB) penetration rate of avitinib (NCT02330367). Methods: Non-small cell lung cancer (NSCLC) patients with the EGFR T790 M mutation were orally administered avitinib (150–300 mg) twice daily for cycles of 28 continuous days. Blood and cerebrospinal fluid samples (2 ml each) were collected on day 29 in available patients with brain metastases, and the tumor response was assessed. Results: Sixteen NSCLC patients were included, of whom nine (60.0%) achieved a partial response, and five (33.3%) achieved stable disease. Median progression-free survival (PFS) and overall survival were 247 days (95% confidence interval (CI): 154.8–339.2) and 536 days (95%CI: 363.6–708.4), respectively. The median intracranial PFS of seven brain metastases patients was 142 days (95% CI 31.1–252.9). Blood and cerebrospinal fluid analysis of five brain metastases patients showed the BBB penetration rate to be 0.046%–0.146%. The most frequent adverse events were mild and reversible hepatic transaminases elevating (10/16, 62.5%) and diarrhea (4/16, 25.0%). Conclusions: Avitinib is well tolerated and efficacious in T790M-positive patients. Its penetrability to the BBB is weak, but it showed good control of asymptomatic brain metastases. Further studies are proceeding.